Solving modified heat equation

In summary, the "Solving modified heat equation" discusses techniques and methods for addressing the modified heat equation, which describes how temperature distribution evolves over time in a medium with varying properties. The article outlines analytical and numerical approaches, including separation of variables, Fourier series, and finite difference methods, to derive solutions under specific boundary and initial conditions. It emphasizes the importance of understanding the underlying physical principles and mathematical frameworks to effectively apply these techniques in practical scenarios, such as materials science and engineering applications.
  • #1
psie
277
32
Homework Statement
Find a solution of the following problem \begin{align} u_t&= u_{xx} - hu,\qquad &0<x<\pi, \ t>0; \\ u(0,t)&=0,u(\pi,t)=1,\qquad &t>0; \\ u(x,0)&=0,\qquad &0<x<\pi.\end{align} Here ##h>0## is a constant.
Relevant Equations
The heat equation in the form ##u_t= u_{xx}## and its solution ##u(x,t)=\sum_{n=1}^\infty b_n e^{-n^2t}\sin nx##.
In my Fourier analysis book, the author introduces some basic PDE problems and how one can solve these using Fourier series. I know how to solve basic heat equation problems, but the above one is different from the previous problems I've worked in terms of the boundary conditions. Using ##u(x,t)=v(x,t)e^{-ht}## I can transform the equation into the heat equation, i.e. ##v_t= v_{xx}## , however, the boundary conditions become $$v(0,t)=0,\quad v(\pi,t)=e^{ht}.$$ I don't know how to deal with non-constant boundary conditions...any ideas on how to proceed?
 
Physics news on Phys.org
  • #2
Think about the long-term steady state. Find a function [itex]u_\infty(x)[/itex] which satisfies [tex]u_\infty'' - hu_\infty = 0[/tex] with [itex]u_\infty(0)= 0[/itex] and [itex]u_\infty(\pi) = 1[/itex]. Then [itex]f(x,t) = u(x,t) - u_\infty(x)[/itex] must satisfy [itex]f_t = f_{xx} - hf[/itex] subject to the self-adjoint boundary condition [itex]f(0,t) = f(\pi,t) = 0[/itex] and the initial condition [itex]f(x,0) = -u_\infty(x)[/itex].
 
  • Like
Likes psie
  • #3
Ok. I found $$u_{\infty}(x)=\frac{\sinh \sqrt{h}x}{\sinh \sqrt{h}\pi}.$$ I still think I have to use the trick ##f(x,t)=e^{-ht}v(x,t)## to turn ##f_t = f_{xx} - hf## into ##v_t = v_{xx}##. The solution to the latter will be $$v(x,t)=\sum_{n=1}^\infty b_n e^{-n^2t}\sin nx.$$ But I'm stuck at how to solve for ##b_n## in $$f(x,0)=v(x,0)=\sum_{n=1}^\infty b_n \sin nx=-\frac{\sinh \sqrt{h}x}{\sinh \sqrt{h}\pi}.$$
 
  • #4
Do you not know how to determine the coefficients [itex]b_n[/itex]?
 
  • #5
pasmith said:
Do you not know how to determine the coefficients [itex]b_n[/itex]?
Right, I don't. I don't see any connection between ##\sinh## and ##\sin## that's useful here.
 
  • #6
If [tex] \sum_{n=1}^\infty b_n \sin nx = f(x), \quad x \in [0, \pi][/tex] then [tex]
b_n = \frac{2}{\pi} \int_0^\pi f(x) \sin nx \,dx.[/tex] This should be derived in any decent textbook on fourier series.

Integrals of the form [itex]\int \sin ax \sinh bx\,dx[/itex] can be done by integratin by parts twice or by expressing everything in terms of exponentials.
 
  • Like
Likes hutchphd, Orodruin and psie
Back
Top